Case Review of Surabaya District Court Decision No. 672/Pdt.G/2016/PN.Sby about Unlawful Sale and Purchase Agreement of Land and Building - Arghie, Ramzi Maulana (Universitas Wijaya Kusuma Surabaya, 2021)
The research, entitled Case Study of Surabaya District Court Decision No. 672/Pdt.G/2016/PN.Sby about Unlawful Sale and Purchase Agreement of Land and Building aims to find out whether or not Dirk Tatipata is said to have defaulted on the Sale and Purchase Agreement (PPJB) of land, which he did with Ronald Sanjaya, how the legal protection for Dirk Tatipata as the party who was harmed by the decision of the Surabaya District Court, This is normative legal research, Based on the results of the study, it can be concluded that legally, it is clear that Dirk Tatipata does not have high bargaining power and is a seller of land and buildings on Jl. Sleep No. 103 that has been done in front and signed by Notary Anita Lucia Kendarto, S.H., M.Kn. with several letters/deeds. Thus, legal resistance is still being carried out by carrying out a lawsuit in the land and building dispute case at the Surabaya District Court, and ending his defeat coupled with a penalty of trial fees and payment for his unlawful actions harmed Ronald Sanjaya as the legal owner of the land and buildingsKeywords: Agreement, Sale, and Purchase of Land and Buildings, Against the Law